Pengembangan Virtual Tour untuk Perpustakaan Universitas Mulawarman - Muhammad Bambang Firdaus; Anjas, Andi; Tejawati, Andi; Taruk, Medi; Wardhana, Reza; Alameka, Faza (METIK JURNAL, 2024)
Advances in technology have now spread to all aspects of life and profession. When archiving, it is appropriate to use a computerized system to make archiving and processing letters easier. but there are still few who take advantage of current technological advances. One of them is the TEXMACO PURWASARI Vocational High School which still archives letters in paper form (hard copy). Manual archiving has weaknesses that pose many risks. By designing the UI/UX of an archival information system, it is hoped that it can solve existing problems. In designing the UI/UX, apply the user center design (UCD) method, which is a method for analyzing the UI/UX design of an electronic archival information system. seen from the system user's perspective, so that the system design is designed according to the user's needs. This research aims, apart from producing a UI/UX design design for an electronic archival information system using the User Centered Design (UCD) method, to also evaluate usability using the system usability scale method (SUS) to measure the feasibility of the Letter Archiving Information System that has been designed. The result of this research is an archival information system design that is equipped with a database design that is tailored to user needs.